Molecular and Biological Aspects of Orthodontic Tooth Movement: Possibilities for Bioengineering Intervention: A Narrative Review - Ioannis A. Tsolakis; Isidora Christopoulou; Symeon Sitaras; Ioannis Lyros; Aliki Rontogianni; Maria Dalampira; Apostolos I. Tsolakis (Bioengineering, 2023)
Background: The current review’s goal is to examine, with a critical eye, the effect of various biomedical parameters on orthodontic tooth movement in an attempt to provide the reader with related mechanisms of this issue focusing on certain key points. Methods: This critical review was conducted using the following keywords in the search strategy: “biomedical molecules”, “biomarkers”, “orthodontics”, “orthodontic tooth movement”, “acceleration”, “gene therapy”, and “stem cells”. Cochrane Library, Medline (PubMed), and Scopus were the databases that were used for the electronic search. Studies published until June 2023 were considered. Results: The use of biomedical approaches in orthodontic tooth movement has been investigated via different procedures and applications. Surgical approaches, biomarkers affecting orthodontic tooth movement, different biological events and mechanisms, RANK, RANK-L, OPG molecular triad, and vibration methods are the basic parameters of biomedical interventions that are examined in the present review. Conclusions: The biomedical approach seems to offer a variety of applications to control orthodontic tooth movement. The scarcity of human studies, as well as the high cost and complexity of these methods, currently limit the available accurate data concerning this issue.